Readiness of Pre-Service Mathematics’ Teachers - Pika Merliza; Selvi Loviana; Bagas Bayu Winata (Peneliti.net, 2020)
This research aims to describe students ' ability to study program of mathematics to be ready to become professional teacher. This research is a qualitative descriptive study in which the research subject is a student of odd microteaching semester 2019/2020 academic year which consisted 8 pre-service teachers selected with purposive sampling technique. Data collection instruments i.e., professional knowledge sheet, practice assessment sheet and interview. Based on the results of data analysis can be described that most students of pre-service mathematics teachers already have readiness to become a professional mathematics teachers seen from two readiness indicators namely, professional knowledge and professional practice.